Psikoedukasi pengasuhan untuk meningkatkan pengetahuan orang tua penyandang disabilitas - Septiani Ayu Nawangsari (Procedia : Studi Kasus dan Intervensi Psikologi, 2022)
Parents have an important role in parenting. The care provided tends to be less appropriate and will have a negative impact on child development. In the case of a community in one RW (Rukun Warga) in Malang, there are some problems regarding parenting that tend to apply one-way communication that aims to make their children independent. Parents tend to limit their children to socialize in the surrounding environment for safety reasons. Both of those decisions are taken on the grounds of wanting to protect the child and form the independence of the child. However, the impact makes the children tend to lack confidence, and are less able to socialize with the environment which will affect their development in the future. The purpose of this study is to increase the knowledge of parents with disabilities about parenting. Assessment methods used are community interviews, observation, questionnaires, and scales. The intervention used is psychoeducation with lecture and roleplay techniques consisting of 6 sessions. The result of the intervention is an increase in the knowledge of parents who have children with special needs. Before treatment, the average knowledge of parents was 2.40 in the less category increased to 4.94 in the good category. The average skill of parents before treatment was 2.17 with the underprivileged category increasing by 3.36 in the quite capable category.